2020
DOI: 10.1038/s41467-020-19600-4
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis demonstrates that integrating polygenic risk scores with modifiable risk factors improves risk prediction

Abstract: Cancer risk is determined by a complex interplay of environmental and heritable factors. Polygenic risk scores (PRS) provide a personalized genetic susceptibility profile that may be leveraged for disease prediction. Using data from the UK Biobank (413,753 individuals; 22,755 incident cancer cases), we quantify the added predictive value of integrating cancer-specific PRS with family history and modifiable risk factors for 16 cancers. We show that incorporating PRS measurably improves prediction accuracy for m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
141
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 53 publications
9
141
0
1
Order By: Relevance
“…Ten-year risk scores are meant to assess short-term risk of being diagnosed with colorectal cancer and would be more efficacious for the general population if modifiable risk factors were incorporated. This current model incorporates non-modifiable risk factors and is best suited for determining baseline colorectal cancer risk without the consideration of highly modifiable risk factors attributed to colorectal cancer [ 59 ]. Finally, we are aware of the population-specific limitations of this study which was restricted to white, Northern-European population.…”
Section: Discussionmentioning
confidence: 99%
“…Ten-year risk scores are meant to assess short-term risk of being diagnosed with colorectal cancer and would be more efficacious for the general population if modifiable risk factors were incorporated. This current model incorporates non-modifiable risk factors and is best suited for determining baseline colorectal cancer risk without the consideration of highly modifiable risk factors attributed to colorectal cancer [ 59 ]. Finally, we are aware of the population-specific limitations of this study which was restricted to white, Northern-European population.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our risk assessment was based solely on genetic variants and family history and did not include other risk factors. Previous studies on UKB showed that lifestyle modifiable risk factors play a pivotal role in cancer prevalence 35 , and a shared lifestyle within families could influence family history with the disease 36 . That might explain the independent association of the family history concerning the genetic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer susceptibility is inherently complex, and polygenetic risk scores using genetic data have been established and show improvement in prediction accuracy for cancer 31 . Our meta-analysis supports a strong association between global repair capacity and cancer risk.…”
Section: Discussionmentioning
confidence: 99%